Agen Biologik Psoriasis Terkini - Nopriyati; Reza Mayasari (Conferences of Medical Sciences Dies Natalis, 2019)
Psoriasis is a chronic inflammatory skin disease with genetic basis, characterized by complex alterations in epidermal growth and differentiation and multiple biochemical, immunologic, and vascular abnormalities. Standard systemic therapies, such as methotrexate, cyclosporine, and acitretin very effective for psoriasis, but associated with significant toxicities. Survey of psoriasis patients in United States shows they have expressed a high level of dissatisfaction with them. Over the past decade, biologic therapies developed as optional therapy of psoriasis. No definition on biologics for psoriasis categories them in old and new therapies. The oldest group of biologics encompasses molecules that target the activation and migration of T cells, alefacept and efalizumab. Therefore, biologics targeting TNFα were developed, and often referred to as first generation biologics, such as etanercept, infliximab, and adalimumab. Second generation biologics emerged from 2009 with antibodies targeting the IL-23/ Th17 pathway. The new biologic agent therapies, like ustekinumab which have targeted in IL-12/ IL-34p40 pathway, secukinumab in IL-17A pathway, ixekizumab in IL-17A pathway, and brodalumab in IL-17RA pathway were developmented in the next year.